PARASITIC FAUNA OF TWO DOMINANT CLARIID (SILURIFORMES) CATFISHES IN A TROPICAL FRESHWATER ECOSYSTEM, NIGERIA - UGBOR, O. N; ODO, G. E.; NWANI, C. D.; OCHANG, S. N; SOMDARE, P.O.; AGBAKWUO, C. A. (Nigerian Journal of Fisheries, 2014)
Three hundred and sixty clariid catfishes comprising of 231 (64.17%) Clarias gariepinus and 129(35.83%) Clarias anguillaris caught with various fishing gears were studied for parasites for a period of 12 months (May 2013 to April 2014) in Anambra River, Nigeria. Out of the 360 fish specimens, 148 (41.1%) fish hosts were infected while 212 (58.89%) were uninfected. There was no significant (p > 0.05) difference in the prevalence of infection between C. gariepinus (44.2%) and C. anguillaris (35.7%). The total number of parasites recovered were 608, comprising two protozoans (Trichodina acuta and Epistylis sp.), two cestodes (Polyonchobothrium clarias and Monobothriode woodlandi) and two nematodes (Rhabdochona congolensis and Procamallanus laevionchus). Protozoan ciliates recovered from the gills and skin of fish hosts had the highest prevalence (25.55%) among the parasites recovered. The rest parasites were recovered from the intestine and the glandular stomach. The relationship of host size (weight and length) and parasite infection showed infection was significant (p < 0.05) in fish of larger weight (126 g+) and length (30 cm+). There was significant (p < 0.05) difference in the infection of sexes, with the males having more infections. Monthly/seasonal patterns of infection varied from one parasite to another. This study provides an overview of the parasites of some clariid species inhabiting the Anambra River.